Growth and Development of Apogamous Adiantum lunulatum Burm. f. Gametophyte from Dry and Humid Areas in Java Island - Novitasari, Risti; Chikmawati, Tatik; Sulistijorini, Sulistijorini (Journal of Tropical Life Science, 2017)
Adiantum lunulatum Burm. f. has been widely used in aesthetic needs and medical fields. Detail information about the life cycle of A. lunulatum is still unknown, particularly about its gametophyte generation. Present work aimed to study and compare the growth and development of the gametophytes of A. lunulatum from dry and humid areas. Research method consists of two stages: (1) Spores were collected from two locations, Pasuruan and Bogor and (2) Spores were planted and observed the growth and development of gametophyte. The result showed that natural habitat of the plant in various dry and humid areas, affecting the rate of growth and development rates of A. lunulatum gametophyte. The gametophyte from the dry area showed faster rate of growth and development than that of humid areas. The spores collected from dry area need 9 weeks for germination, growth, and development while the spores of humid area took 22 weeks.